2016
DOI: 10.1016/j.ijdevneu.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Schneiderian first rank symptoms in schizophrenia: A developmental neuroscience evaluation

Abstract: Schizophrenia patients satisfying the criteria of presence of first rank symptoms represent a distinct neurodevelopmental subgroup with associated features of predominantly positive symptoms, significantly lower neurotrophin levels, aberrant resting state brain activity in the heteromodal association cortex and performing poorer on self-monitoring tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Changes to the rest/task difference on neuronal measures could thus manifest as a failure to demarcate self and other, or self disorder. For instance, the typical human ability to engage in self-referential processing more reliably than comparable non-self-referential processing may depend on a typical rest-task difference in the brain, which is then impaired in schizophrenia (25,29,30). The basic model of self thus incorporates the view that sense of self is a metacognitive faculty that is compromised in schizophrenia (54, 55) while also situating this faculty in relationship to the resting state activity of the brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes to the rest/task difference on neuronal measures could thus manifest as a failure to demarcate self and other, or self disorder. For instance, the typical human ability to engage in self-referential processing more reliably than comparable non-self-referential processing may depend on a typical rest-task difference in the brain, which is then impaired in schizophrenia (25,29,30). The basic model of self thus incorporates the view that sense of self is a metacognitive faculty that is compromised in schizophrenia (54, 55) while also situating this faculty in relationship to the resting state activity of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Source monitoring accounted for the most articles, which were predominantly from Ford and colleagues, who used a simple task with (1) a talk condition, and (2) a listen condition in which the recording of the talk condition is played back to the participant (36-40, 42, 43, 45, 46). In addition to these paradigms, some studies presented resting-state data and/or data on the difference between the resting state and task-related activity (16,27,29,47,48).…”
Section: Paradigms or Tasks Probing The Self And Behavioral Datamentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8 ] Electroencephalographic (EEG) activity, particularly resting-state activity, has been proposed as potential biomarkers for diagnosing SCZ. [ 9 10 11 12 ] Besides the advantage of being cost-effective and of unparalleled temporal resolution inherent to EEG, studying resting-state activity enhances the ease and reproducibility of the procedure. In fact, some studies have shown resting-state EEG to differentiate positive and negative symptom (NS) subgroups of SCZ.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have noted significantly higher levels of additional psychotic symptoms in individuals with schizophrenia who experience FRS in comparison to those who do not experience FRS (Jablensky, 1992; Tikka, Nizamie, Das, Agarwal, & Goyal, 2016; van Rooijen et al, 2017). However, past research has not addressed whether passivity symptoms (in contrast to FRS auditory hallucinations) are particularly associated with other types of psychotic symptoms, nor whether passivity symptoms might be particularly strongly associated with specific types of psychotic symptoms.…”
mentioning
confidence: 98%